The Land of stories - Beyond the kingdoms - Colfer, Chris 1990- (Little, Brown and Company, 2016)
"The Masked Man possesses a powerful magic potion that turns every book it touches into a portal, and he is recruiting an army of literature's greatest villains! So begins a race through the magical Land of Oz, the fantastical world of Neverland, the madness of Wonderland, and beyond. Can twins Alex and Conner catch up to the Masked Man?"--
Sequel to: The Land of stories - A Grimm warning
Includes excerpt from The land of stories: an author's odyssey
Keywords: Twins / Juvenile fiction; Characters and characteristics in literature / Juvenile fiction; Magic / Juvenile fiction; Siblings / Juvenile fiction; Fairy tales; Characters in literature / Fiction; Frères et surs / Romans, nouvelles, etc. pour la jeunesse; Contes de fées; fairy tales; Siblings; Characters and characteristics in literature; Magic; Twins; Magic / Fiction; Brothers and sisters / Fiction; Twins / Fiction; Adventure fiction; Action and adventure fiction; Fantasy fiction; Fiction; Juvenile works; Kinderbuch